LINGUISTIC SYMBOLS IN THE POLICE’S BAP OF LINGUISTS FROM AN ANTHROPOHISTORICAL SEMIOTIC PERSPECTIVE - Firmansyah, Erfi; Muliastuti, Liliana; Anwar, Miftahulkhairah (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
This study analyses the linguistic symbol instruments in the Investigative Report (BAP) of Language Experts in criminal cases related to the ITE Law at Polda Metro Jaya using an Anthrohistorical semiotic approach. The study attempts to reveal the linguistic aspects in the BAP reflecting power relations, gender bias, and ideological constructions underlying the legal process. The use of legal terminology and formal language structures strengthens the position of the authority of legal institutions, while gender bias is identified in terms that reinforce certain stereotypes. The results of the study explain that the case analysed contributed to the linguistic symbol instruments in criminal cases related to violations of the ITE Law at Polda Metro Jaya. The linguistic symbol instruments are the words ’main-main dan dengar-dengar’. The words ’main-main dan dengar-dengar’ indicate linguistic symbols related to the ITE Law. In disclosing the linguistic symbols of the BAP in the police in its application, of course, it is still necessary to pay attention to the social, cultural, and historical contexts that influence the birth of the text in the context of its use.